Biopolitical strategies in contemporary institutions: Critical analysis of mechanisms of control and protection of human rights - Flota, Sheila Yajaira Barnet; Torres, Arturo Gonzalez; Hernández, María Luisa Pereira; Montero, Fátima Yaraset Mendoza (Edelweiss Applied Science and Technology, 2025)
This research aimed to strengthen knowledge about institutional biopolitical power and to describe strategies to develop social justice and human rights. The methodology used was qualitative in approach, but as a tool or instrument. Qualitative techniques were used through a critical review of the literature on biopolitical theories, in order to find patterns on how they are applied in the institution. Five key elements were found in their application: institutional control and regulation, management of subjectivities and behaviors, administration of resources and capacities, optimization technologies and control and regulation of life trajectories. The study found that biopolitics functions as a tool to regulate key social dimensions such as health, education and security.